Synthesis, structural, mechanical, and biological properties of HAp-ZrO2-hBN biocomposites for bone regeneration applications. Issue 21 (1st November 2021) - Gautam, Amarendra; Gautam, Chandkiram; Mishra, Monalisa; Sahu, Swetapadma; Nanda, Reetuparna; Kisan, Bikash; Gautam, Rakesh Kumar; Prakash, Ravi; Sharma, Kriti; Singh, Divya; Gautam, Satyam Shivam
Abstract: Nowadays researchers are much interested in bioceramics for their use as biological implants. Researchers have succeeded to derive few bioceramic materials which show good biological response with living tissues. Few of the bioceramics are zirconia, hexagonal boron nitride and hydroxyapatite. Herein, the effects of zirconia nanoparticles and hexagonal boron nitride nanosheets in hydroxyapatite powder on the structural, mechanical, and biological properties were investigated. In this study, the formation of a potential composite with desired mechanical and biological properties is strongly anticipated. The present study is also proposed to provide further faces to improve osteogenic properties of the scaffolding material without altering the established mechanical and biological properties. Three different compositions in the system [(95-x)HAp-x(ZrO2 )-5hBN] (x = 10, 20, 30) were prepared using a simple solid-state reaction technique. In the samples, significant phase was identified for HAp [Calcium Phosphate Hydroxide: Ca5 (PO4 )3 (OH)]. SEM analysis of the composites revealed well-connected and uniform distribution of ZrO2 and HAp nanoparticles on h-BN sheets. The composite samples 65H30Z5B9h (65HAp-30ZrO2 -5hBN sintered at 900 °C) and 65H30Z5B1T (65HAp-30ZrO2 -5hBN sintered at 1000 °C) showed improved mechanical and tribological behaviors. These samples exhibited excellent mechanical properties like compressive strength, Young's modulus, toughness and density. The obtained values were 2.154 MPa, 0.0182 MPa, 553.82 MJ/m 3, 2.29 g/cm 3 for 65H30Z5B9h and 3.798 MPa, 0.0832 MPa, 231.59 MJ/m 3, 2.31 g/cm 3 for 65H30Z5B1T respectively. Cytotoxicity of the composites was studied on Drosophila fly and Mice calvarial osteoblasts cells at five different concentrations. Toxic effect of the composite 65H30Z5B1T on the fly was confirmed by phenotypic observations, trypan blue staining, pupal count, and larval crawling speed. Composite 65H30Z5B1T was found to be toxic in this study, but the composite 65H30Z5B9h was not. Further, cell viability, alkaline phosphates, and mineralization tests confirmed non-toxic property and enhanced osteogenic activities for the composite sample 65H30Z5B9h.